A tale of magic ... - Colfer, Chris 1990- (Little, Brown and Company, 2019)
Fourteen-year-old Brystal Evergreen risks everything by opposing her kingdom's repression of women, but Madame Weatherberry, seeing her potential, invites her to a school where she hopes to change the world's perception of magic
Prequel to The Land of Stories series
Keywords: Children's stories; Fantasy fiction; Books and reading; Fairies; Families; Fantasy; Magic; Sex role; Sex role / Juvenile fiction; Books and reading / Juvenile fiction; Family / Juvenile fiction; Magic / Juvenile fiction; Fairies / Juvenile fiction; Fantasy fiction / Juvenile fiction; Sex role / Fiction; Books and reading / Fiction; Family life / Fiction; Magic / Fiction; Fairies / Fiction; Fictional Work; Fiction; Juvenile works; Romans; Kinderbuch